An analysis of verb groups in legal discourse: Implications for teaching English for specific purposes - Gocheco, Paulina M. (Animo Repository, 2011)
The analysis of verb groups provides another dimension in reading and understanding legal discourse. The verb group is the main constituent of the verb phrase in a sentence structure, which provides the necessary connection between the Subject and the Predicate of a sentence in a legal provision. In general, legal language is highly nominal; however, it may be helpful to see how these nominals co-occur with another important constituent, the verb. This may only be seen in a more appropriate perspective through the identification of the verb groups and its relation with the nominals in a provision. To provide a framework for the analysis of the verb group, the sub-categorization of Burton-Roberts (1997) was used: contrastive, intransitive, intensive, complex transitive, and prepositional. Specific examples of texts were drawn from the corpus of fourteen legal provisions on property ownership and other related real estate laws drawn from the Philippine Civil Code. The study attempts to explain the peculiarity of legal language through a careful examination of the verb group, a structure that is often neglected in legal discourse analysis. In view of ESP training, the study attempts to empower the lay audience (the real estate practitioner and the teacher, in particular) through the acquisition of knowledge, information, and the ability to read and interpret relevant legal provisions.